Passive all‐sky imaging radar in the HF regime with WWV and the first station of the Long Wavelength Array. Issue 5 (5th September 2013) - Helmboldt, J. F.; Clarke, T. E.; Craig, J.; Dowell, J. D.; Ellingson, S. W.; Hartman, J. M.; Hicks, B. C.; Kassim, N. E.; Taylor, G. B.; Wolfe, C. N.
<x xml:space="preserve">Abstract</x> [1] We present a new passive, bistatic high‐frequency (HF) radar system consisting of the transmitters for the radio station WWV and the dipole antenna array that comprises the first station of the Long Wavelength Array (LWA) or "LWA1." We demonstrate that these two existing facilities, which are operated for separate purposes, can be used together as a unique HF radar imager, capable of monitoring the entire visible sky. In this paper, we describe in detail the techniques used to develop all‐sky radar capability at 10, 15, and 20 MHz. We show that this radar system can be a useful tool for probing ionospheric structure and its effect on over‐the‐horizon (OTH) geolocation. The LWA1+WWV radar system appears to be especially adept at detecting and characterizing structures associated with sporadic‐E. In addition, we also demonstrate how this system may be used for long‐distance, OTH mapping of terrain/ocean HF reflectivity. Finally, we discuss the potential improvements in the utility of these applications as more LWA stations are added.